2004
DOI: 10.1097/00126334-200402010-00012
|View full text |Cite
|
Sign up to set email alerts
|

Immunoprophylaxis to Prevent Mother-to-Child Transmission of HIV-1

Abstract: Antiretroviral therapy can profoundly reduce the risk of mother-to-child transmission (MTCT) of HIV, but the drugs have a relatively short half-life and should thus be administered throughout breast-feeding to optimally prevent postnatal infection of the infant. The potential toxicities and the development of resistance may limit the long-term efficacy of antiretroviral prophylaxis, and a safe and effective active/passive immunoprophylaxis regimen, begun at birth, and potentially overlapping with interpartum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 45 publications
1
29
0
1
Order By: Relevance
“…[145][146][147] They demonstrated that passive transfer of a mAb cocktail (F105, 2F5 and 2G12) completely protected pregnant mothers against intravenous SHIV-vpu+ challenge after delivery. The infants subsequently born to these infected mothers who received the mAbs indirectly across the placenta from their mothers and received another dose of antibody cocktail followed by oral challenge with SHIV-vpu+ were also completely protected against the infection.…”
Section: Protection Against Hiv-1 Infectionmentioning
confidence: 99%
“…[145][146][147] They demonstrated that passive transfer of a mAb cocktail (F105, 2F5 and 2G12) completely protected pregnant mothers against intravenous SHIV-vpu+ challenge after delivery. The infants subsequently born to these infected mothers who received the mAbs indirectly across the placenta from their mothers and received another dose of antibody cocktail followed by oral challenge with SHIV-vpu+ were also completely protected against the infection.…”
Section: Protection Against Hiv-1 Infectionmentioning
confidence: 99%
“…The Env targets defined by these MAbs include the CD4 binding site (CD4bs) of gp120 (4, 10, 27, 38, 39), a conserved peptidoglycan region of variable loops 1 and 2 (V1V2) (21,35,36), the membrane proximal region of gp41 (23,32), and most recently, a peptidoglycan epitope in the V3 region of gp120 (24,35). The potency and breadth of these new human MAbs have also suggested the possibility of their clinical use as therapeutic agents (30, 31) or as agents to prevent HIV-1 infection, including the prevention of mother-to-child transmission (22,26). HIV-1 prevention could also be mediated by MAbs as microbicides (33) or by systemic levels of antibodies generated by gene-based vectors (2, 12).…”
mentioning
confidence: 99%
“…L'environnement de la grossesse est donc loin de représenter un vide immunitaire pour le VIH, puisqu'il doit de fait composer avec la pré-sence « non pas de un mais bien de deux » systèmes immuns distincts, systèmes qui semblent tous deux capables de contribuer de manière significative à la résistance de l'hôte contre l'infection. Les résultats de ces études ont également amené d'influents groupes de chercheurs et de cliniciens à considé-rer la vaccination ou l'immunoprophylaxie (c'est-à-dire anticorps monoclonaux) comme des stratégies valables susceptibles d'endiguer la TME du VIH, particulièrement dans les situations où les ressources sont limitées et où l'on ne peut que difficilement offrir de substitut à l'allaitement maternel [28]. En effet, des études initialement prometteuses ont montré que l'immunisation passive à l'aide d'anticorps monoclonaux pouvait prévenir la TME d'un hybride des virus de l'immunodéficience simienne et humaine (SHIV) via le lait maternel chez le singe Rhésus [29].…”
Section: Transmission Mère-enfant Du Vih Et Réponse Immunitaireunclassified